Attaining Employability Skills by Focusing on Information Competencies: How Far Are We? - Špiranec, Sonja (Array, 2014)
In the employment context, employers give more and more priority to candidates with generic competencies. Numerous studies suggest that information competencies have an important role in generic competencies. However, studies performed in Croatia indicate unsystematic and sporadic presence of information competencies in curricula. The aim of this paper is to analyze the information competencies in graduate study programs at the University of Zagreb. In order to cover the largest number of enrolled students, as the sample for analysis 20% of graduate programs with the largest number of enrolled students were selected from each scientific field (biomedicine, biotechnology, engineering, humanities, natural sciences and social sciences) with the exception of arts study program. These top 20% of graduate programs enroll a total of 41% of the students' quota for the entire University of Zagreb. A total of 27 master study programs were analyzed with a total of 2735 courses. The research results provide a presentation of the current situation and recommendations for the optimization of information competencies in the graduate curriculum at the university level